Chapter 17 Researching Family Lives, Schooling and Structural Inequality in Rural Punjab The Power of a Habitus Listening Guide - Naveed, Arif (Taylor & Francis, 2024)
This chapter advances a novel theoretic-methodological approach to the analysis of qualitative data. The aim is to achieve a deeper understanding of the relationship between social inequality and educational outcomes in post-colonial rural Southern contexts. It operationalises the Habitus Listening Guide (Arnot & Naveed, 2014) derived from Bourdieu's theory of cultural reproduction and contemporary narrative theory. The chapter describes the application of four listenings using a dialogic, multi-layered, analysis of interview transcripts. It uncovers the polyphonic voices of four members of Munawar Hussain's family, describing the impact of the rural social structure on their educational and occupational biographies. Inter-narrativity is generated through repeated listenings of the social structure, of paired father-mother and son-daughter and then of father-son and mother-daughter narratives, and a final mythic-ritual listening which makes audible when religious beliefs are called into play. These beliefs either contribute to the maintenance of poverty and social inequality, and yet inspire strategies to disrupt power structures through education as a religious duty. Each listening reveals the dialectic relationship between the hierarchal post-colonial social order and its school system, and the family's gendered and generational educational aspirations, strategies, and outcomes.